Ovule and embryo-sac development in almond - Korkmaz Y.; Gülcan R.; Misirli A.; Askin M.A. (XI GREMPA Seminar on Pistachios and Almonds, 2001)
In some varieties, degenerations occurring in relation to development of embryo sac and ovule at different stages might be a cause of fruitlessness. In fruit growing, to understand problems about this matter, knowledge is needed about embryo sac and ovule development. For this purpose, this study was designed. Tuono almond variety was used in this experiment. Sections from fixed samples were prepared by using the paraffin method. It was observed that ovule and integuments did not develop during the dormancy period. In the balloon stage, megaspore differentation began. At bloom, the embryo sac elongated and expanded. Embryo sac degeneration occurred probably on the fifth day on un-pollinated flowers.
11. GREMPA Seminar on Pistachios and Almonds, 1999/09/01-04, Sanliurfa (Turkey)